Determinação da capacidade de carga turística para trilha principal de acesso à Cachoeira de Deus : Parque Municipal Turístico-ecológico de Penedo, Itatiaia-RJ - Seabra, Lilia dos Santos (2009)
This study has as objective to determine the tourist load capacity to the main access trail to the Cachoeira de Deus (God s Waterfall), in the Penedo s Tourist Ecological Municipal Park in Itatiaia - RJ, applying the CIFUENTES methodology (1992). So, the ecotourism term has been defined, emphasized its emergency in the social and economical areas. It also considered its nature as a merchandise and the urge of a planning need. Concerning the load capacity studies, this concept was historically reviewed and recent studies for tourist proposals were discussed. The tourist social - economical profile was traced by the analyses of 192 interviews that also supplied their opinions, desires and perceptions about the visited area. In this way, the CIFUENTES methodology (1992), was increased. To determine the tourist load capacity in its three levels (physical load capacity, real load capacity and effective/permissible load capacity), physical, ecological, environmental and management variables were analyzed for the main access trail to the Cachoeira de Deus. Regarding the physical load capacity, this work has taken advantages of the variables: the time of the trail visitation, the size of each visitor s group and the distance among them, the duration of the visits and the physical space occupied by a visitor in the trail. To determine the real load capacity, this work has used the rainfall values, soil erosion levels; trails access difficulty degree and fauna disturbance variables. Regarding the effective / permissible load capacity, data concerning infrastructures, devices and the staff needed for administration in order to assist the objectives of the Park has been acquired. A special highlight was given to the physical variable soil erodibility increasing it with the studies of bulk density and organic matter content. This was not used by CIFUENTES (1992) in his methodology and it was possible to obtain more satisfactory and reliable results. As conclusion of the study, the physical load capacity determination obtained the result of 720 visitors / day, and to the real load capacity determination the result was 129 visitors/ day. Due to the absence of infrastructure, staff and devices, the effective/ permissible capacity load could not be established, so the trail's tourist load capacity study is based on 129 visitors / day, until the necessary devices, infrastructures and staff for the trail are supplied.